Local Socio-Economic and Communication Dynamics in Facing Climate Change in Bangkala District, Jeneponto Regency - Alimin Alwi; Najamuddin, Najamuddin; Nurfauziah Kasmin (International Journal of Education, Vocational and Social Science, 2025)
This study aims to analyze the dynamics of local socio-economic and communication in dealing with the impacts of climate change in Bangkala District, Jeneponto Regency. Climate change has brought major challenges to communities, especially in the agriculture and fisheries sectors, which depend on stable environmental conditions. In dealing with these changes, communities develop various adaptation strategies involving economic, social, and communication aspects. This study uses a qualitative approach with a descriptive method, where data is collected through interviews, observations, and documentation to gain a deep understanding of the adaptation strategies implemented by the community. The results of the study show that communities implement various adaptation strategies, such as diversifying income sources, utilizing digital technology to monitor weather and environmental conditions, and strengthening social networks through community cooperation. In addition, community communication patterns have changed from traditional methods to the use of digital media, such as weather applications and online communication groups, which help them in decision making related to agricultural and fisheries activities.